1995
DOI: 10.1042/bj3050791
|View full text |Cite
|
Sign up to set email alerts
|

The effect of histone H1 and DNA methylation on transcription

Abstract: We have previously shown that DNA methylation acts as a focus for the formation of inactive chromatin in vivo. We have investigated the mechanism further by in vitro transcription of a template containing two tRNA genes and an extensive (G+C)-rich sequence characteristic of a CpG island. The extent of transcription from the unmethylated or fully methylated template was assayed in the presence of varied levels of histone H1. The transcriptional activity of both templates was inhibited by increasing amounts of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
2

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 50 publications
(53 reference statements)
1
17
0
2
Order By: Relevance
“…It follows that the preferential inhibition of transcription from the methylated template seen in their study could result from the weakness of the methylated promoter, rather than discriminatory binding by H1. It is not known whether the factors responsible for driving transcription of the tRNA gene in the study by Johnson et al (27) are directly affected by methylation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It follows that the preferential inhibition of transcription from the methylated template seen in their study could result from the weakness of the methylated promoter, rather than discriminatory binding by H1. It is not known whether the factors responsible for driving transcription of the tRNA gene in the study by Johnson et al (27) are directly affected by methylation.…”
Section: Discussionmentioning
confidence: 95%
“…The activity, known as MDBP-2, was originally identified as a 40-kDa protein that was very tissue specific in distribution (26) but was subsequently attributed to a dimer of H1 (25). Finally, Johnson et al (27) have concluded that H1 preferentially inhibits transcription from a methylated template, and they propose that methylated sites on the DNA serve as foci for long range chromatin condensation mediated by H1.…”
mentioning
confidence: 99%
“…These results suggest a direct, site-speci®c eect of methylation on transcriptional activation. However, CpG methylation may also exert an indirect eect on the accessibility of DNA to protein factors, since the nucleosomal organization of transcription factor binding sites implies a role for chromatin structure in determining DNA accessibility (Ben-Hattar et al, 1989;Weih et al, 1991;Johnson et al, 1995). In either case, the high density of CpGs within putative BRCA1 regulatory elements represents a considerable target at which DNA methylation can either directly or indirectly exert a functional eect (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently purified MDBP2 was found to be histone H1 (34). Though some investigators have proposed preferential binding of histone H1 to methylated DNA and thereby implicated it in methylation-mediated transcriptional repression (35,36), others have found this not to be the case (37). MeCP-1 binds in vitro to DNA containing at least 12 symmetrically methylated CpGs (20), whereas MeCP-2 can bind to a single methylated CpG (31).…”
Section: Methylation Of Whole Plasmid or 22-kb Upstream Promoter Butmentioning
confidence: 99%